Inflammatory Myoglandular Polyps: A Case Series of Four Patients and Review of the Literature - Shoji Hirasaki; Hiromitsu Kanzaki; Minoru Matsubara; Seiyuu Suzuki (Gastroenterology Research and Practice)
Background. Inflammatory myoglandular polyp (IMGP) is a nonneoplastic colorectal polyp. Only a small number of cases have been reported, and the pathogenesis remains unclear. Methods. We analyzed colonoscopy and histologic findings in 4 patients with IMGP. Histologic confirmation of the inflammatory granulation tissue in the lamina propria, proliferation of smooth muscle, and hyperplastic glands with variable cystic changes formed the criteria for the selection of patients. Results. We treated four cases of IMGP and reviewed the literature on this disease. Three cases were located in the sigmoid colon or descending colon. All 4 polyps were identified as red, pedunculated lesions. All 4 cases had no symptoms. In two cases, endoscopic findings of polyps were necessary to be differentiated from juvenile polyps. Conclusions. Pedunculated lesions are the main pattern of IMGP. An analysis of endoscopic and histologic features in IMGP of the colorectum revealed that colonic IMGPs resembled juvenile polyps. On colonoscopy, IMGP should generally be taken into consideration as a differential diagnosis of peduncular polyp.